The Rebellion of Anōš Āzād - JACKSON BONNER, Michael Richard (Historia i Świat, 2016)
This article analyses the sources of the Rebellion of Anōš Āzād, son of Xusrō Anōšīrvān. The truth of what happened during this important period of Iranian history may never be known. But historical sources have transmitted fragments of the story from various different perspectives – often in lacunary form. Reading the relevant sources together, and analysing them, allows us to determine why some sources are fragmentary or deliberately misleading. It is possible to infer why certain authors, such as Procopius and Dinawari, might have been motivated to suppress or distort certain details also.